The Potential Utilizing ChatGPT for Education and Teaching Students: Understanding, Prospects, Challenges, and Utilization" - Oktaria, Renti; Ali, Irhamni; Putra, Purwanto (Educative: Jurnal Ilmiah Pendidikan, 2023)
This research aims to analyze the development of the ChatGPT topic in the context of its utilization and the challenges in supporting 21st-century education and learning programs that require the development of learning media as well as mapping the risks associated with the presence of AI (Artificial Intelligence) phenomenon, specifically ChatGPT. This requires the development of learning media as well as the mapping of risks associated with the presence of AI phenomenon, specifically ChatGPT. The method used in this study is a literature review related to ChatGPT, gathered from the Google database using the Google Advanced search strategy. The keywords "ChatGPT," "education," and "learning" were used to access various publications, particularly national and international scholarly articles that discuss relevant topics. The research findings generally indicate that ChatGPT is currently popular and dynamic, and it is predicted to continue growing in the future. However, discussions specifically related to ChatGPT in the field of education and learning are still the subject of debate, with both supporters and dissenters presenting rational arguments. Several examples demonstrate the significant positive benefits of ChatGPT's presence. To avoid confusion, it is crucial to establish policies formulated by authorized entities and implement them nationally with various supporting regulations.